2019
DOI: 10.3389/fendo.2019.00090
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Associations of Testosterone With Metabolic Traits

Abstract: Background: Testosterone levels are differentially linked with diabetes risk in men and women: lower testosterone levels in men and higher testosterone levels in women are associated with type 2 diabetes, though, the mechanisms are not fully clear. We addressed sex-specific links between testosterone and major pathogenetic mechanisms of diabetes.Methods: We analyzed data of 623 subjects (202 male, 345 female without, and 76 female with oral contraceptive therapy [OCT]) for whom insulin sensitivity and insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…These results are congruent with previous MR studies in the UKBB showing positive links between higher BioT and increased lean mass (24,48), reduced fat mass (48), and lower glucose (24). However, they are only partly consistent with observational data demonstrating inverse associations between circulating testosterone and risk of metabolic syndrome in men (31,32,(49)(50)(51), as well as clinical findings in men with physiologic or chemically induced hypogonadism, who were shown to be at increased risk of developing obesity and IR, as well as T2DM (8,52,53). On the other hand, our data are aligned with RCTs of testosterone therapy in men, which reported benefits on adiposity as reflected by lower HIPadjBMI herein, as well as diminished fasting glucose levels and T2D risk (54,55).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are congruent with previous MR studies in the UKBB showing positive links between higher BioT and increased lean mass (24,48), reduced fat mass (48), and lower glucose (24). However, they are only partly consistent with observational data demonstrating inverse associations between circulating testosterone and risk of metabolic syndrome in men (31,32,(49)(50)(51), as well as clinical findings in men with physiologic or chemically induced hypogonadism, who were shown to be at increased risk of developing obesity and IR, as well as T2DM (8,52,53). On the other hand, our data are aligned with RCTs of testosterone therapy in men, which reported benefits on adiposity as reflected by lower HIPadjBMI herein, as well as diminished fasting glucose levels and T2D risk (54,55).…”
Section: Discussionsupporting
confidence: 89%
“…These results extend the MR findings of Ruth et al ( 24 ), which provided suggestive evidence of a causal link between higher BioT and elevated WHRadjBMI using anthropometric data from a smaller GWAS ( 29 ). They also complement results from observational studies, which have generally reported positive associations between higher androgen levels and central obesity, CVD risk burden, and T2D risk in women ( 11 , 12 , 13 , 30 , 31 , 32 , 33 , 34 ). The mechanisms accounting for these links are unclear.…”
Section: Discussionsupporting
confidence: 77%
“…Physiologically, sex hormones are involved in the regulation of glucose metabolism and are essential for maintenance of glucose homeostasis [ 2 ]. In men, testosterone is linked to insulin sensitivity and glycemic control [ 3 ]. Accordingly, in males there is a correlation between testosterone deficiency and the prevalence of prediabetes [ 4 ] and insulin resistance [ 5 ], meaning testosterone has favorable effects on glucose metabolism in males.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term effects on women’s health of significantly increased levels of testosterone and cortisol compared to the control group and women that had preeclampsia several weeks postpartum is yet to be investigated. However, previous studies have shown that increased testosterone levels in women are associated with insulin resistance, higher glucose concentrations and increased body fat—a precursor of developing metabolic syndrome more rapidly than women without a history of GDM [ 12 ].…”
Section: Discussionmentioning
confidence: 99%